2015
DOI: 10.1093/ntr/ntv133
|View full text |Cite
|
Sign up to set email alerts
|

A Single Controlled Exposure to Secondhand Smoke May Not Alter Thrombogenesis or Trigger Platelet Activation

Abstract: While there are abundant data showing enhanced thrombogenesis and platelet activation following repeated exposure to SHS, our study suggests that a single exposure does not appear to significantly alter thrombin kinetics nor result in platelet activation. The effects of SHS on thrombogenesis might be nonlinear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Thromboxane, another marker of platelet activation, is also increased in subjects exposed to ETS, in some cases to levels observed in active smokers [37]. The preponderance of data suggests a non-linear relationship between ETS and thrombogenesis [38]. Notably, a study which exposed 10 healthy nonsmoking males to 20 min of ETS revealed that ETS affected endothelial cell counts (mean values: 2.8 ± 0.9 before exposure and 3.7 + 1.1 after exposure, mean difference 0.9, 95% CI: 0 −1.8) and platelet aggregate ratios (mean values: 0.87 ± 0.06 before exposure and 0.78 ± 0.07 after exposure to passive smoking, mean difference 0.09, 95% CI: 0.03—0.15) similarly to those of active smokers [36].…”
Section: Ets and Thrombosis: Clinical And Experimental Observationsmentioning
confidence: 99%
“…Thromboxane, another marker of platelet activation, is also increased in subjects exposed to ETS, in some cases to levels observed in active smokers [37]. The preponderance of data suggests a non-linear relationship between ETS and thrombogenesis [38]. Notably, a study which exposed 10 healthy nonsmoking males to 20 min of ETS revealed that ETS affected endothelial cell counts (mean values: 2.8 ± 0.9 before exposure and 3.7 + 1.1 after exposure, mean difference 0.9, 95% CI: 0 −1.8) and platelet aggregate ratios (mean values: 0.87 ± 0.06 before exposure and 0.78 ± 0.07 after exposure to passive smoking, mean difference 0.09, 95% CI: 0.03—0.15) similarly to those of active smokers [36].…”
Section: Ets and Thrombosis: Clinical And Experimental Observationsmentioning
confidence: 99%
“…The biological markers for the purpose of assessing the exposure of environmental tobacco smoke are identified as nicotine and cotinine (Benowitz,1999). tobacco smoke exposure develops athero-thrombosis by means of platelet adhesion inflammation, endothelial dysfunction and plaque instability (Srikanth et al, 2016). The toxic primary components of environmental tobacco smoke (side stream smoke) are conscientious for major morbidity and mortality due cardiovascular diseases generation to generation causing pro atherogenic milieu.…”
Section: Environmental Tobacco Smoke (Ets)mentioning
confidence: 99%